Analysis of the Influence of Prices and Promotions on Consumer Behavior in Decision Making for Study Program Selection at Universitas Dhyana Pura - Sukmawati, Mia Dana; Joko Adinegara, I Gusti Ngurah; Komalasari, Yeyen; Trimurti, Christimulia Purnama (Eastasouth Institute, 2024)
The study aims to analyze the influence of prices and promotions on consumer behaviour, and how consumers' behaviours influence consumer decisions in decision making choosing a study program at Universitas Dhyana Pura. The research methods used in this research are quantitative methods and associative research designs. The total sample in this study was 97 respondents. Data collection techniques are questionnaires, observations and interviews (Path analysis). Research results show that prices and promotions have a significant and positive influence on consumer behavior. Prices also have a significant positive influence on decision-making for the selection of study programmes at Universitas Dhyana Pura. Promotions have a positive but non-significant impact on the choice of study programme decisions at the University. In addition, prices and promotions have a positive and significant influence on the decision to choose a course of study through consumer behavior mediation, which suggests that competitive pricing strategies and effective promotions can influence consumers' behaviour in choosing a course at Universitas Dhyana Pura.